In silico information processing for DNA computing readout method based on DNA engine opticon 2 system - Mohamed Saaid, Muhammad Faiz; Ibrahim, Zuwairie (Institute of Electrical and Electronics Engineering (IEEE), 2007)
In this paper, a novel readout approach for the Hamiltonian path problem (HPP) in DNA computing based on the real-time polymerase chain reaction (PCR) is proposed. Based on this approach, real-time amplification was performed with the TaqMan probes and the TaqMan detection mechanism was exploited for the design and development of the proposed readout approach. The readout approach consists of two phases: real-time amplification in vitro using TaqMan- based real-time PCR, followed by information processing in silico to assess the results of real-time amplification, which in turn, enables the extraction of the Hamiltonian path. In this paper, instead of using manual clustering of two different reactions in real-time PCR, a computer system is developed such that the clustering can be done automatically. This clustering process can be done quickly based on the number of nodes in the HPP problems and the TaqMan reactions and the data obtained previously is used to extract the correct Hamiltonian path.